Flugbrand- und Hartbrandanfälligkeit von Sommergersten unter simuliertem Befall - Müller, Dr. Karl-Josef (kassel university press GmbH, Kassel, 2005)
Fifty-five spring barley varieties from the German official varieties list were tested for their susceptibility to loose smut (Ustilago nuda) and covered smut (Ustilago hordei) under a simulation of natural infection conditions. For loose smut infection cv. ‘Lawina’ with about 5 % infected plants was used as spreader. In the trial with covered smut 1kg of seeds were shaken with 1g of spores to contaminate the surface of barley seeds before sowing. Only ‘Steffi’ stayed absolutely free from loose smut during two infection cycles at two locations. With an average of 12.6 % plants with loose smut ‘Danuta’ was the most susceptible. Most susceptible to covered smut were ‘Tunika’ with 13.2 % and hulless ‘Taiga’ with 15 % infected plants. Thirteen varieties remained free of covered smut. Among these ‘Auriga’, ‘Hendrix’, ‘Jacinta’ and ‘Sigrid’ showed a low loose smut infection with always less than 1 %. No correlation between loose and covered smut susceptibility could be detected. Under organic farming a variety with a susceptibility below 1 % under natural infection could be acceptable for maintaining seeds on farm, but for organic seed multiplication during all generations from breeding to production more loose smut resistant varieties are necessary to fulfil the demands of current seed regulations.